Uncharted waters: Exploring coastal recreation impacts, coping behaviors, and attitudes towards offshore wind energy development in the United States. (May 2021) - Ferguson, Michael D.; Evensen, Darrick; Ferguson, Lauren A.; Bidwell, David; Firestone, Jeremy; Dooley, Tasha L.; Mitchell, Clayton R.
Abstract: United States offshore wind energy development (OWD) is poised to expand significantly in the coming decade as a result of substantial wind resources adjacent to large population and coastal load centers. A significant portion of OWD infrastructure may be sited within or adjacent to parks and protected areas, raising concerns about the potential social, situational, and ecological impacts upon coastal recreation. This novel study investigated the influence of perceived recreation impact and coping behaviors upon coastal recreationists' general attitudes towards potential OWD at the New Hampshire seacoast. On-site surveys were used to collect data from New Hampshire coastal recreationists from June to September of 2019 ( n = 553). The study sample's perceptions towards the acceptance, support, fit, and recreation impact of OWD at the New Hampshire Seacoast was largely supportive and positive. The overall sample perceived the presence of OWD would not cause them to alter or substitute their recreation activities, behaviors, or experiences. Moreover, structural equation modeling suggests perceived recreation impact and coping behaviors are significant predictors of general attitudes towards OWD. Further, a lack of measurable effect from photo-elicitation priming suggests viewshed impacts and the spatial proximity of OWD siting did not have a significant influence upon general attitudes towards OWD. This research offers critical insights into the theories of stress-coping and landscape fit and calls into question the assumption that situational factors such as OWD act as a stressor on coastal recreation. This study found that OWD will likely have little impact on aggregate coastal recreation visitation, and in some instances, may even amplify visitation. This research demonstrates the importance of evaluating coastal recreationists' perceptions, behaviors, and attitudes from a social-ecological approach when initiating OWD projects in the United States and abroad.